2011
DOI: 10.1007/s11605-011-1606-7
|View full text |Cite
|
Sign up to set email alerts
|

The Changes of Pro-opiomelanocortin Neurons in Type 2 Diabetes Mellitus Rats After Ileal Transposition: The Role of POMC Neurons

Abstract: More pro-opiomelanocortin neurons in the hypothalamus of diabetes rats were activated after ileal transposition. These data suggest a potential important role for pro-opiomelanocortin neurons in the resolution of diabetes after IT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…According to the results, rats in the operated groups showed significantly decreased AUC ITT values at early and long-term points, indicating the ability of SG surgeries to improve IS. This result is consistent with previous studies [22][23][24][25]. However, ITT only roughly estimates IS and could not further assess hepatic and peripheral IS.…”
Section: Discussionsupporting
confidence: 90%
“…According to the results, rats in the operated groups showed significantly decreased AUC ITT values at early and long-term points, indicating the ability of SG surgeries to improve IS. This result is consistent with previous studies [22][23][24][25]. However, ITT only roughly estimates IS and could not further assess hepatic and peripheral IS.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, another study from our laboratory detected more activated proopiomelanocortin neurons after IT in GK rats and found this upregulation to be associated with improved glucose homeostasis. 23 Other reported explanations for early improvement in insulin sensitivity after gastric bypass included upregulation of insulin signaling pathway and enhanced intestinal gluconeogenesis. Bonhomme et al 24 reported increased levels of phosphorylated insulin receptor substrates 1 and 2 in skeletal muscle and liver tissues and proposed that these contributed to the reversal of diabetes after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The 2016 ADA treatment guidelines even recommend GLP-1 receptor agonists in the treatment of poorly controlled T2DM 6. Our previous study found that the level of GLP-1 in the cerebrospinal fluid (CSF) was significantly elevated after IT, and the pro-opiomelanocortin (POMC) neurons in arcuate nucleus were activated 7. The POMC neuron is a specific population of arcuate nucleus neurons in the hypothalamus 8.…”
Section: Introductionmentioning
confidence: 99%